S Sharia-Compliant Entrepreneurship: An Innovative Model for Islamic University Business Incubators - Hasanuddin, Muhammad; Kusuma, Suteja Wira Dana (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2024)
This study examines the unique challenges faced by Muslim entrepreneurs in aligning their businesses with sharia principles, introducing the concept of “Muslimpreneurship,” where profit-seeking is intertwined with sharia compliance and a broader sense of purpose. It emphasizes the role of Islamic universities in fostering entrepreneurship while maintaining adherence to Islamic values, highlighting distinctions between conventional and Islamic University Business Incubators (UBIs) in principle and practice. The proposed model advocates for sustained relationships with incubatees beyond the incubation phase, supporting them through continuous monitoring, mentorship, and consultancy. The research methodology consists of a literature review focusing on university business incubators, Muslim entrepreneurship, and Islamic business ethics; qualitative interviews with incubator managers from the IPB Business Incubator, Malang University, and Unpad Business Incubator to explore how these institutions support Muslim entrepreneurs and integrate sharia principles; and site visits to observe the practical application of Islamic values within these incubators. This approach aims to develop a conceptual framework for an Islamic University Incubator, offering both theoretical insights and practical recommendations for creating incubators that align with Islamic ethical standards.s.